A quantum degenerate Bose-Fermi mixture of 41K and 6Li - Wu, Yu-Ping; Yao, Xing-Can; Pan, Jian-Wei (Journal of physics. B, Atomic, molecular and optical physics, 2017)
We report a new apparatus for the study of two-species quantum degenerate mixture of 41 K and 6 Li atoms. We develop and combine several advanced cooling techniques to achieve both a large atom number and high phase space density of the two-species atom clouds. Furthermore, we build a high efficiency two-species magnetic transport system to transfer atom clouds from the 3D magneto-optical-trap chamber to a full glass science chamber of an extreme high vacuum environment and good optical access. We perform a forced radio-frequency evaporative cooling for 41 K atoms while the 6 Li atoms are sympathetically cooled in an optically plugged magnetic trap. Finally, we achieve the simultaneous quantum degeneracy for the 41 K and 6 Li atoms. The Bose-Einstein condensate of 41 K has 1.4 × 10 5 atoms with a condensate fraction of about 62%, while the degenerate Fermi gas of 6 Li has a total atom number of 5.4 × 10 5 at 0.25 Fermi temperature.